2022
DOI: 10.1111/iej.13789
|View full text |Cite
|
Sign up to set email alerts
|

Impact of systemic health on treatment outcomes in endodontics

Abstract: Background:The healing of periapical lesions after root canal treatment (RCT) is not the result of the curative action of the treatment. The process of healing begins with inflammation, and is resolved by the clearance of the immunogen that induces the immune response. Then, the periapical tissue itself carries out the healing of the periapical lesion, by repair or by a combination of repair and regeneration, depending on the host's reparative response working properly. The ultimate objective of RCT is to achi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
27
0
14

Year Published

2022
2022
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(41 citation statements)
references
References 160 publications
0
27
0
14
Order By: Relevance
“…2 Root canal therapy is internationally recognized as the first choice at present, but there is still a failure rate of 7% and 14%, secondary root canal treatment had an even lower success rate of 77%. [3][4][5] Enterococcus faecalis (E. faecalis) is the bacteria with the highest detection rate in the cases of failed root canal therapy, and it is also the most important pathogen in the progression of PAP, it has cytolysin, adhesive protein, gelatinase, lipoteichoic acid (LTA) and other virulence factors. 6,7 E. faecalis can form biofilm in the root canal wall, apical triangle, apical divergence and bifurcated root canal.…”
Section: Introductionmentioning
confidence: 99%
“…2 Root canal therapy is internationally recognized as the first choice at present, but there is still a failure rate of 7% and 14%, secondary root canal treatment had an even lower success rate of 77%. [3][4][5] Enterococcus faecalis (E. faecalis) is the bacteria with the highest detection rate in the cases of failed root canal therapy, and it is also the most important pathogen in the progression of PAP, it has cytolysin, adhesive protein, gelatinase, lipoteichoic acid (LTA) and other virulence factors. 6,7 E. faecalis can form biofilm in the root canal wall, apical triangle, apical divergence and bifurcated root canal.…”
Section: Introductionmentioning
confidence: 99%
“…In the present study, we demonstrate a significant reduction of hsCRP and mCRP at 1-and 6 months after RCT in AP individuals with baseline cardiovascular risk, showing a mechanistic link between AP and systemic inflammation. Apical periodontitis and cardiovascular diseases share common risk factors, such as genetic polymorphisms, smoking, and diabetes, increasing susceptibility to chronic inflammation (Segura-Egea et al, 2023). Previously, our research group reported that LGSI markers were significantly higher in AP individuals compared to healthy controls (Garrido et al, 2019).…”
Section: Discussionmentioning
confidence: 86%
“…Conversely, it has been suggested that diabetes, cardiovascular disease, inflammatory diseases, osteoporosis exacerbate AP and prevent or delay its healing. This cycle has been found to be linked to an increase in IL‐β and TNF‐α levels (Cintra et al., 2016, 2017; Segura‐Egea et al., 2023; Sehirli et al., 2019; Zhang et al., 2016). Besides, this accumulating evidence underscores the potential of AP to trigger a systemic immune response, affect distant organs, and influence the overall patient health.…”
Section: Discussionmentioning
confidence: 99%